2010
DOI: 10.1002/jor.21223
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low‐intensity pulsed ultrasound upon diabetic fracture healing

Abstract: ABSTRACT:In the United States, over 17 million people are diagnosed with type 1 diabetes mellitus (DM) with its inherent morbidity of delayed bone healing and nonunion. Recent studies demonstrate the utility of pulsed low-intensity ultrasound (LIPUS) to facilitate fracture healing. The current study evaluated the effects of daily application of LIPUS on mid-diaphyseal femoral fracture growth factor expression, cartilage formation, and neovascularization in DM and non-DM BB Wistar rats. Polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 46 publications
2
36
1
2
Order By: Relevance
“…Diabetic rats with optimal glycemic control did not experience these changes, and the mechanical properties of the bone were similar to non-diabetic animals [23] . Poorly controlled DM also decreases important cytokine production and reduces new blood vessel formation at the site of callus [24] .…”
Section: General Issuesmentioning
confidence: 99%
“…Diabetic rats with optimal glycemic control did not experience these changes, and the mechanical properties of the bone were similar to non-diabetic animals [23] . Poorly controlled DM also decreases important cytokine production and reduces new blood vessel formation at the site of callus [24] .…”
Section: General Issuesmentioning
confidence: 99%
“…Low intensity pulsed US have been used for diagnostic purposes for a long time and been shown to have a positive effect on bone regeneration and fracture healing. 5,12,37 Bone remodeling is a dynamic and continuous process. It has already been shown in different studies that NO modulates fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors showed that, especially DM type 1, leads to a decreased proliferative activity of osteoblast progenitor cells and gene expression, an impairment in osteoblast function and osteoblast response to signaling cues, and an increased osteoclast proliferation, resulting in lower bone mineral density (BMD) and increased risk of fractures [3][4][5]. Moreover, it has been demonstrated that, after the occurrence of a fracture, the whole process of bone healing is impaired and delayed, which can result in nonunion fractures or pseudoarthrosis [3,6].…”
Section: Introductionmentioning
confidence: 98%
“…Some therapeutic interventions have been described by their osteogenic potential, including lowintensity therapeutic ultrasound [6,7], electromagnetic fields [8], and application of bone morphogenetic protein (BMP) [9]. In addition, a significant body of evidence has now accumulated demonstrating that photobiomodulation (PBM) also has a positive effect on bone tissue metabolism and on fracture consolidation [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%